Interdependence and business cycle transmission between South Africa and the USA, UK, Japan and Germany - Mugova, Terrence Tafadzwa (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
The process of globalisation has had a large impact on the world economy over the past three decades. Economic globalisation has manifested itself in the increasing integration of goods and services through international trade and the integration of financial markets. As a consequence the existence of co-movements in economic variables of different countries has become more evident. The extent to which globalisation causes a country's economy to move together with the rest of the world concerns policy-makers. When such co-movement is significant, the influence of policy-makers on their respective domestic economies is significantly reduced. South Africa re-entered the international economy in the early 1990s when the forces of globalisation, especially for developing countries, seemed to gain momentum. Empirical research such as Kabundi and Loots (2005) found strong evidence of international co-movement between the world business cycle and the South African business cycle, particularly following South Africa's integration into the global economy. This study examines the relationship and interdependence between South Africa and four of its major developed trading partners. More particularly, the study examines the question of whether business cycles are transmitted from Germany, Japan, US and UK to South Africa, and/or from South Africa to Germany, Japan, the US and UK. The study employs structural vector autoregressive (SVARs) models to analyse monthly data from 1980:01"“2008:04 on industrial production, producer prices, short-term interest rates and real effective exchange rates. The results show that South Africa benefits from economic growth in both the UK and US. They also indicate significant price transmission from Germany and Japan to South Africa, with transmission in the opposite direction being statistically insignificant. The impulse response graphs show that a positive one standard deviation shock to both German and Japanese producer prices has a negative impact on South African output (industrial production) growth. Furthermore, South African monetary policy is relatively unresponsive to international monetary policy stances. The findings of this study indicate that South African policymakers need to take into consideration economic performance of the country's major trading partners, with particular emphasis on the UK and US economies.
Keywords: International economic relations -- Developing countries; Business cycles -- Developing countries; Economic development -- Developing countries; Industrial policy -- Developing countries; International finance